Virtual Reality for People with Visual Impairments in the development of Left-Right Discrimination Skills: A Systematic Mapping Study - Moraes Júnior, José Martônio Lopes de; Viana, Windson; Façanha, Agebson Rocha (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Integrating digital technologies, particularly Virtual Reality (VR) games, into Orientation and Mobility (OM) training has shown significant potential for enhancing the rehabilitation process for People with Visual Impairments (PVI). These technologies provide immersive and interactive experiences that foster greater autonomy and independence. In OM training, left-right discrimination helps individuals establish spatial relationships and shapes the foundation for learning more complex orientation skills. This systematic mapping study examines how VR games can be used to train left-right discrimination abilities in PVI, offering them new experiences. We reviewed 758 articles and selected 19 studies that highlight the importance of considering all types of visual impairments, involving PVI in the development process, and accounting for their existing skills when designing game interactions.